2013
DOI: 10.1021/ja408405f
|View full text |Cite
|
Sign up to set email alerts
|

Order–Disorder Transition of Dipolar Rotor in a Crystalline Molecular Gyrotop and Its Optical Change

Abstract: Successful control of the orientation of the π-electron systems in media has been achieved in certain liquid crystals, making them applicable to devices for optical systems because of the variation in the optical properties with the orientation of the π-electron system. However, because of close packing, changing the orientation of molecules in the crystalline state is usually difficult. A macrocage molecule with a bridged thiophene rotor was synthesized as a molecular gyrotop having a dipolar rotor, given tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 45 publications
2
72
0
Order By: Relevance
“…The concomitant presence of the tight binding and the dynamic supramolecular complex should be of great interest for the theoretical studies, and the helical environment found on the Hirshfeld surface is of special interest for its effect on the dynamic motion. Furthermore, because the peapod bearing of discrete molecules provides access to a homochiral columnar assembly in the crystalline solid state, an interesting possibility of synchronized orientations of single-axis motion of the peapod bearing may be exploited (35,36). The manipulation of the periodicity of C 60 sites in the tubular column through designing the interdigitated chains as a spacer is also of great interest (37).…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant presence of the tight binding and the dynamic supramolecular complex should be of great interest for the theoretical studies, and the helical environment found on the Hirshfeld surface is of special interest for its effect on the dynamic motion. Furthermore, because the peapod bearing of discrete molecules provides access to a homochiral columnar assembly in the crystalline solid state, an interesting possibility of synchronized orientations of single-axis motion of the peapod bearing may be exploited (35,36). The manipulation of the periodicity of C 60 sites in the tubular column through designing the interdigitated chains as a spacer is also of great interest (37).…”
Section: Discussionmentioning
confidence: 99%
“…Such rotation demonstrates promise as a new class of mechanical switches, compasses, and gyroscopes. [189][190][191][192][193] When the rotor units contain an electric dipole, amphidynamic crystals may also provide an avenue for tunable dielectrics. [194][195][196] Solid-state NMR techniques are useful characterization methods to determine molecular order and the gyroscopic dynamics within amphidynamic crystals when rotors contain atoms that occupy multiple magnetically non-equivalent sites.…”
Section: Acs Nanomentioning
confidence: 99%
“…[9] Form olecular crystals,t he dielectric transition between low-and high-dielectric states is established by the reorientation transformation of polar components between static (that is,f rozen) and dynamic (motional) phases,w hich are often accompanied by as tructural phase transition (PT). [12][13][14][15][16][17][18][19][20] Among the various stimuli, temperature is the most frequently used trigger.I nc ontrast, fewer results have been reported on responsive materials that are triggered by stimuli besides temperature. [12][13][14][15][16][17][18][19][20] Among the various stimuli, temperature is the most frequently used trigger.I nc ontrast, fewer results have been reported on responsive materials that are triggered by stimuli besides temperature.…”
mentioning
confidence: 99%